El corte de rocas ornamentales con discos diamantados: influencia de las características petrográficas de la roca - A. Rodríguez-Rey; L. M. Suárez del Río; L. Calleja; V. G Ruiz de Argandoña (Materiales de Construccion, 1998)
This paper follows another one published in the preceding number of this same journal, that reviewed some scientific papers on the influence of the factors of the cutting equipments (machinery, cutting characteristics, disks, etc) on the efficiency of the cutting process of ornamental rocks with diamond disks. In this second part, the inner rock characteristics (mineralogy, texture and voids) affecting the cutting performance are considered. Some rock classifications based on their cuttability proposed by some authors and Institutions are also reviewed.